Factors affecting E-learning among students in UniMAP - Gayathri Murugan (School of Business Innovation and Technopreneurship, University Malaysia Perlis, 2012)
E-learning is widely used in universities and other organizarions all over the world, either to support classroom learning or as a specialized methodology on its own merit. The university Malaysia Perlis (UniMAP) is no exception to this changing world trend. This research is basically an attempt to investigate the factors that influence the effectiveness of the e-learning system in UniMAP . The subject of this study are the students from the School of Computer & Communication Engineering of UniMAP who were selected randomly. The primary data source is the questionnaires that were distributed to these students. The analysis of data was carried out using SPSS mode.